SP0115 Crystals and joints. (1st June 2001) - Doherty, M
Abstract : Primary metabolic disease may predispose to the deposition of a variety of crystals in and around joints, most notably calcium pyrophosphate (CPPD) and apatite. Crystal associated musculoskeletal symptoms may be the presentation of such disease. Renal failure additionally predisposes to urate and oxalate crystal deposition. In most disease states the principal mechanisms relate to elevated ionic products. There is good evidence that hyperparathyroidism, hypomagnesaemia, haemochromatosis and hypophosphatasia predispose to CPPD deposition; data are less convincing for hypothyroidism, Wilson's disease and other putative associations. Clinical features are acute "pseudogout" attacks in association with polyarticular chondrocalcinosis (CC). Haemochromatosis is exceptional in additionally causing structural joint change and chronic symptoms. Patients <55 years presenting with recurrent acute attacks and polyarticular CC should be screened for metabolic disease (minimum = serum ferritin, magnesium, calcium, alkaline phosphatase). Treatment of the primary disease, however, probably little influences the outcome of CPPD and CC. All these diseases increase extracellular pyrophosphate levels; effects on CPPD crystal nucleation and dissolution, however, are also evident. Rare monogenic familial CC may shortly be explained as primary metabolic disorders of pyrophosphate metabolism involving several enzyme systems. Milder forms of hypophosphatasia may cause calcific periarthritis due to apatite deposition, in association with axial and peripheral ossifying enthesopathy. Hyperparathyroidism (primary, but particularly secondary or tertiary in patients with renal failure) may also cause this. With renal failure crystal deposits may be massive ("tumoral calcinosis") and both form and resolve with treatment over short periods of time. By far the more common consequence of renal failure, however, is urate crystal deposition. This may result in chronic tophaceous gout and acute attacks. Treatment may prove difficult but allopurinol remains the principal agent. Oxalate crystals can deposit in many tissues, including muscles and joints, and possibly cause myalgia and acute inflammatory episodes in chronic dialysis patients. Reference: Jones A, et al . Diseases associated with CPPD deposition disease. Semin Arthritis Rheum 1992;22:188–202